Implementation of Counseling by the Binmas Unit to Prevent Crime of Theft by Aggrivated Circumstances at the Cianjur Police Department - Priscilla Tissy Atotoy (Advances in Police Science Research Journal, 2021)
The crime of theft with weighting is one of the third highest crimes in Cianjur Regency. This criminal act is based on various forms of perpetrator patterns, time patterns, patterns of crime scenes, and target patterns. Various efforts have been made by the binmas unit by taking preventive actions to the community through counseling on kamtibmas. The problem is the implementation of counseling by the binmas unit to prevent criminal acts of theft by weighting it at the Cianjur Police, factors that hinder the implementation of counseling, the efforts made to increase the role of the binmas unit. In writing this thesis the method used is a qualitative approach. Based on the writer's findings in the field, basically the tasks carried out by the Binmas unit have been carried out. Binmas unit officers carry out their role by providing information about theft with a weight to the community and to increase the role and partnership between the police and the community. In discussing this problem the writer uses Communication Theory, Role Theory, and Management Theory along with management elements, namely 6M (man, money, materials, machines, methods, markets), the concept of extension, the concept of polmas, and the concept of theft with weighting. The conclusion of this study is that the prevention of criminal acts of theft with weight can be through counseling. Suggestions that need to be considered are to increase preventive action through counseling, increase the ability or basic provisions to members of the Binmas unit and invite the community to do positive things so that people who are often negligent in maintaining security and environmental order are aware and more careful.